Antigen complex of Coccidioides immitis which elicits a precipitin antibody response in patients. - Cole, G T (1991)
The occurrence in patients of elevated levels of immunoglobulin M (IgM) precipitin antibody to Coccidioides immitis antigens, which are commonly detected by the immunodiffusion-tube precipitin (TP) assay, is suggestive of primary nondisseminating coccidioidomycosis. We previously demonstrated that the concanavalin A-bound mycelial culture filtrate plus lysate preparation is a source of at least two TP antibody-reactive antigens (TP-Ags), which were identified by sodium dodecyl sulfate-polyacrylamide gel electrophoresis as 120- and 110-kDa fractions. Evidence is presented here that the crude filtrate plus lysate preparation contains additional lectin-bound, TP antibody-reactive fractions as well as a component which elicits a complement fixation antibody response in patients. The 120- and 110-kDa fractions were isolated from the antigen complex and further characterized in this paper. Both TP-Ags are glycoproteins and have been shown by immunoelectron microscopy to be colocalized within cytoplasmic vesicles and the wall of spherules. Deglycosylation of these TP-Ags by sodium periodate treatment resulted in a loss in patients of 82 to 95% of IgM adsorption to the antigens as detected by the enzyme-linked immunosorbent assay (ELISA). Comparison of their carbohydrate compositions revealed that mannose and glucose are the predominant monosaccharides of both TP-Ags but only the 120-kDa fraction contained 3-O-methylmannose, a sugar which appears to be unique to C. immitis among the systemic fungal pathogens. We previously showed that 3-O-methylmannose is at least partly responsible for the reactivity of IgM antibody with the 120-kDa TP-Ag. Good correlation was shown between results of immunodiffusion-TP assays and ELISAs of IgM response to both the 120- and 110-kDa fractions by using 70 serum samples from patients with proved coccidioidomycosis. However, only 2.8% (3 of 109) of the serum samples from patients with other mycoses and nonmycotic infections showed IgM adsorption to the 120-kDa TP-Ag as detected by the ELISA, while 21.1% (23 of 109) showed IgM adsorption to the 110-kDa TP-Ag. The 120-kDa TP-Ag is a potentially valuable serodiagnostic reagent for detection of specific IgM by ELISA in patients with primary coccidioidomycosis.